Maximilian Hell (1720-92) and the ends of Jesuit science in Enlightenment Europe - Aspaas, Per Pippin (Jesuit studies, 2020)
The Viennese Jesuit court astronomer Maximilian Hell was a nodal figure in the eighteenth-century circulation of knowledge. He was already famous by the time of his celebrated 1769 expedition for the observation of the transit of Venus in northern Scandinavia. However, the 1773 suppression of his order forced Hell to develop ingenious strategies of accommodation to changing international and domestic circumstances. Through a study of his career in local, regional, imperial, and global contexts, this book sheds new light on the complex relationship between the Enlightenment, Catholicism, administrative and academic reform in the Habsburg monarchy, and the practices and ends of cultivating science in the Republic of Letters around the end of the first era of the Society of Jesus